2011
DOI: 10.1088/0957-4484/22/9/095302
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal domain lithography for regularly arranged artificial magnetic out-of-plane monodomains in Au/Co/Au layers

Abstract: Regularly arranged magnetic out-of-plane patterns in continuous and flat films are promising for applications in data storage technology (bit patterned media) or transport of individual magnetic particles. Whereas topographic magnetic structures are fabricated by standard lithographical techniques, the fabrication of regularly arranged artificial domains in topographically flat films is difficult, since the free energy minimization determines the existence, shape, and regularity of domains. Here we show that k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…Ga + ‐fluence‐induced increase of Kerr rotation was also observed . We have demonstrated that controlled changes of the magnetic anisotropy realized by ion bombardment with different fluences may be applied for production of magnetic films with parameters attractive for hard disc technology or transport of magnetic (commercially available) markers (beads) .…”
Section: Magnetic Anisotropy Engineering and Rpt In A Single Cobalt Lmentioning
confidence: 74%
“…Ga + ‐fluence‐induced increase of Kerr rotation was also observed . We have demonstrated that controlled changes of the magnetic anisotropy realized by ion bombardment with different fluences may be applied for production of magnetic films with parameters attractive for hard disc technology or transport of magnetic (commercially available) markers (beads) .…”
Section: Magnetic Anisotropy Engineering and Rpt In A Single Cobalt Lmentioning
confidence: 74%
“…In Figure 2b, the measured H C is plotted as a function of the x -position for both stripes. A monotonic decrease of coercive field with F is observed, which is caused by the reduction of the interface anisotropy due to modification of Co/Au and Au/Co interfaces through the increasing fluence of the 10-keV He + ions [19,25,26]. Comparing the H C ( F ) and H C ( x ) dependencies for the two stripes with different gradients (Figure 2b,c), it can be seen that the H C ( F ) basically does not depend on d F /d x .…”
Section: Resultsmentioning
confidence: 99%
“…The base pressure during sputtering was < 1 × 10 −6  Pa with Ar process gas (Ar partial pressure approximately 10 −2  Pa). The Co thickness t Co was chosen to be well above the critical thickness where the Co layer becomes superpara- or paramagnetic after light-ion bombardment [19] and at the same time thin enough to preserve a large PMA. Moreover, t Co selected here ensures that the magnetization reversal in the unbombarded Au/Co/Au system in a perpendicular magnetic field develops primarily by DW movement [2].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In magnetoresistive sensor stacks (sensors based on the giant magnetoresistance effect or magnetic tunnel junctions) with magnetic reference electrodes pinned by exchange bias, for example, the pinning direction can be set to an arbitrary direction after completion of the deposition process essentially without changing the magnetoresistive effect amplitude [11][12][13]. Its possible use in creating magnetic logic elements has similarly been proven [14] as its potential to create engineered domain patterns by ion beam writing or when combined with lithographical techniques [1,4,[15][16][17]. The latter patterns have shown to be useful for magnetic particle transport by moving domain walls [18], by changing potential energy landscapes associated with the stray fields above the engineered domains [19,20] or by topological transport [21].…”
Section: Introductionmentioning
confidence: 99%